2019
DOI: 10.1021/acs.energyfuels.9b00867
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl Porphyrin Speciation Based on Submegahertz Ligand Proton Hyperfine Couplings

Abstract: The speciation of vanadyl (VO2+) porphyrins in crude oil (vanadyl petroporphyrins) is an area of ongoing interest in petroleomics. In this paper, we describe a method for the speciation of vanadyl porphyrins that uses electron nuclear double resonance (ENDOR), a high-resolution electron paramagnetic resonance (EPR) spectroscopic technique. We use 1H ENDOR to measure hyperfine couplings between ligand protons and the paramagnetic vanadyl ion as small as about 0.15 MHz. From the measured hyperfine couplings, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
(86 reference statements)
3
18
0
Order By: Relevance
“…More importantly, a recent study by Mannikko and Stoll reported the use of sub-megahertz hyperfine couplings to speciate the substitution pattern in a series of vanadyl porphyrin model compounds. 64…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, a recent study by Mannikko and Stoll reported the use of sub-megahertz hyperfine couplings to speciate the substitution pattern in a series of vanadyl porphyrin model compounds. 64…”
Section: Resultsmentioning
confidence: 99%
“…For future research, a detailed analysis of the structure and surrounding of vanadyl complexes (porphyrinic and nonporphyrinic) and radicals by more sophisticated EPR techniques would provide clues to the fabrication receipts and the evolution/degradation of embalming materials. First, electron nuclear double resonance (ENDOR) spectroscopy will provide additional information on the evolution of VO-P complexes by probing hyperfine interactions with 1 H nuclei of metallic complexes and radicals . Second, pulse-EPR methods will allow direct measurements of relaxation times T 1 and T 2 and measurement of small hyperfine intera c tions with 14 N, 13 C, 31 P, and 33 S nuclei. ,, However, the ease of use of standard continuous-wave X-band EPR spectroscopy (recording a spectrum takes only a few minutes) and the ubiquity of vanadyl geoporphyrins VO-P and radicals in bitumen open the door to the easy characterization of bitumen in all types of archeological artifacts.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The values A// = 2.6 MHz and AꞱ = 0.3 MHz measured for VO-P correspond to the values known for the hydrogen Hmeso of porphyrin in vanadyl porpyrin complexes. 33,34 It must be noticed that additional ENDOR features that would be expected at A// = 1.3 MHz and AꞱ = 0.4 MHz for hydrogen of pyrrole groups, 34,35 are not observed in our ENDOR spectra.…”
Section: Resultsmentioning
confidence: 61%